1999
DOI: 10.1021/bi981933z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ligand Substitution in Ferrocytochrome c Folding

Abstract: The ligand substitutions that occur during the folding of ferrocytochrome c [Fe(II)cyt c] have been monitored by transient absorption spectroscopy. The folding reaction was triggered by photoinduced electron transfer to unfolded Fe(III)cyt c in guanidine hydrochloride (GuHCl) solutions. Assignments of ligation states were made by reference to the spectra of the imidazole and methionine adducts of N-acetylated microperoxidase 8. At pH 7, the heme in unfolded Fe(II)cyt c is ligated by native His18 and HisX (X = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 43 publications
11
82
4
Order By: Relevance
“…We obtained the methionine-heme spectrum by adding B 1 (l) to the known deoxyheme spectrum until the result generated the best ®t to reference Fe(II) heme-methionine spectra; we obtained reference spectra from our measurements of native cytochrome c and from published sources. 3,4,42 We found very good agreement between the observed transient spectra and the ®t to Scheme I. The slow t 4 process, which is presumably related to refolding/unfolding kinetics omitted from Scheme I, erodes the quality of ®ts that include millisecond time-scales (although it does not affect our analysis of the very fast heme-Met80 loop kinetics).…”
Section: Kinetic Modeling Of Spectrasupporting
confidence: 65%
See 1 more Smart Citation
“…We obtained the methionine-heme spectrum by adding B 1 (l) to the known deoxyheme spectrum until the result generated the best ®t to reference Fe(II) heme-methionine spectra; we obtained reference spectra from our measurements of native cytochrome c and from published sources. 3,4,42 We found very good agreement between the observed transient spectra and the ®t to Scheme I. The slow t 4 process, which is presumably related to refolding/unfolding kinetics omitted from Scheme I, erodes the quality of ®ts that include millisecond time-scales (although it does not affect our analysis of the very fast heme-Met80 loop kinetics).…”
Section: Kinetic Modeling Of Spectrasupporting
confidence: 65%
“…Results agreed with published Fe(II) hemehistidine spectra. 3,4,42 The methionine-liganded heme spectrum is also a ®xed input, obtained as follows: The fastest exponential decay t 1 in the data corresponds to the replacement of the deoxyheme by the methionine complex. Thus B 1 (l) is proportional to the deoxyheme minus methionine-heme difference spectrum.…”
Section: Kinetic Modeling Of Spectramentioning
confidence: 99%
“…The absence of strongly shifted peaks in the 1 Fe II -Cyt c Folding. Fe II -Cyt cЈ folding was initiated by rapid electron injection (Ϸ100 s) into unfolded oxidized protein ([GuHCl] ϭ 2.02-2.54 M) after two-photon laser excitation of NADH (43,44). Under these conditions, heme reduction is slower than binding of the nonnative sixth ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical examination has revealed that the oxidized His 18 -His 82 form is highly disordered, and it is proposed that this high level of disorder facilitates rapid rearrangement to His 18 -Met 80 upon reduction (8). Heme-ligand exchange reactions between methionine and histidine residues were first observed during the in vitro folding and unfolding reactions of oxidized (9 -11) and reduced (12,13) horse heart cytochrome c. His 18 and Met 80 are the axial heme ligands in native cytochrome c in both oxidation states. In unfolded cytochrome c, the proximal histidine (His 18 ) remains an axial ligand by virtue of its proximity to Cys 15 and Cys 17 , which form the thioether linkages to the porphyrin ring (14 -16).…”
Section: -Met 106 Ligation Similar To Reduced C Domains This Form Imentioning
confidence: 99%